The Internal Realities of Individuals With Type 2 Diabetes: Mediators Influencing Self-Management Beliefs via Grounded Theory Approach - Yogarabindranath Swarna Nantha; Shamsul Haque; Azriel Abisheg Paul Chelliah; Anuar Zaini Md Zain; Gan Kim Yen (SAGE Publishing, 2020)
Background: There has been an unabated rise in the prevalence of type 2 diabetes (T2D) worldwide. Although T2D is highly preventable, these trends suggest that a paradigm change is much needed in the way both clinicians and policy makers view what effective T2D strategies conventionally entail. Hence, it is becoming increasingly clear that T2D patients require more than just a pharmacological approach to their disease. Evidence indicate that culturally specific mediators can help foster better self-management practices. We intend to discover psychosocial mediators that influence and support self-management beliefs in T2D patients. Methods: We adopted the grounded theory approach to guide in-depth interviews with T2D patients and health care professionals (HCP) at a regional primary care clinic in Malaysia. Twenty-four T2D patients and 10 HCPs were recruited through purposive sampling method to examine the inner psychological narratives about how they perceive and what they believe beliefs about the disease. Two focus group discussions were also were conducted for data triangulation. Results: A functional framework for the psychosocial mediators influencing self-management beliefs in T2D patients was designed and characterized by 4 major processes: (1) health promotion, (2) personal expectations, (3) person-centered care, and (4) psychosocial support. The fulfillment of patients' personal expectations is central to better self-management beliefs. Conclusions: Positive emotional states are important in providing a positive environment to nurture self-management practices. A person-centered consultation that focuses on empathy and cultural sensitivities has the potential to foster behavioral change required to sustain self-care practices.